A study to find out if staff knows what is carbon footprint: a case study in UiTM, Melaka City Campus / Nur Fatihah Mohamad Razali and Nurfaizatul Farhana Sahrom - Mohamad Razali, Nur Fatihah; Sahrom, Nurfaizatul Farhana (Faculty of Administrative Science and Policy Studies, 2012)
This study will determine the awareness of Universiti Teknologi Mara staffs towards carbon footprint issue. The study was based on a survey carried out from questionnaire that is involving 170 staff. By using the descriptive analysis the awareness of UiTM Melaka City Campus are examined. The findings show that the awareness among staff is high. However, the factor of carbon footprint is the most contributing element that influences the majority of staff to be aware on carbon footprint compared to effect and also reduction of carbon footprint. The findings of this study will help the university to change their attitude and behaviour in reducing the percentage of carbon dioxide emission.